Production of L-Lactic Acid Using Various Carbon Sources by Enterococcus Gallinarum EB1 - Cheong, Weng Chung (2002)
This study reports on the production of L-lactic acid using a locally isolated bacteria. Bacteria were screened and isolated from POME sludge, kitchen refuse, leachate biomass, soil and fermented milk. Five bacteria shown positive result in the preliminary test and only one bacteria which was isolated from POME effluent shown the highest lactic acid production. Using shake flask culture, 18.0 g/L of L-lactic acid was produced from 20.0 g/L glucose . The selectivity of lactic acid produced by the bacteria was 99.8% compared to other organic acids. This indicated that the bacteria can be use for the production of L-Lactic acid. Using the BIOLOG system, the bacteria was identified belonging to the family Enterococcus gallinarum and named as Enterococcus gallinarum EB1. Morphologically, the bacteria is cocci-shaped and in chains or grouped. The optimal growth condition for the bacteria was at pH 6 and temperature 37°C where at this condition, the bacteria able to produced highest lactic acid yield at 1.9 g/g using glucose as substrate. The organic acids composition was dependent on the pH and temperature. In an anaerobic batch fermentation to produce lactic acid using four types of substrates (glucose, kitchen refuse, sago starch and cooked rice), the highest lactic acid production was 45.0 g/L. From the experiment, the bacteria was able to convert the kitchen refuse into lactic acid at 45.2 g/L and small amount of other organic acids. The comparison was also done with other substrates to show that the bacteria able to utilise kitchen refuse in lactic acid production. In the recovery process of lactic acid, the best method was to use H₂SO₄ prior to evaporation at 90°C with 3mmHg vacuum pressure. H₂SO₄ able to free lactic acid from lactate salts formed in the fermentation because the use of NaOH to control pH in the bioreactor throughout the fermentation process. The evaporation method able to achieved 86.76% lactic acid recovery yield from the fermentation broth. It was the highest recovery yield recorded in evaporation compared to other evaporation method with additional of solvents (propanol and butanol) with temperature at 90°C and pressure around 3mmHg.